2010
DOI: 10.1128/iai.01020-09
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Live Candidate Vaccines for Paratuberculosis in Animal Models and Macrophages

Abstract: Mycobacterium avium subsp. paratuberculosis (basonym M. paratuberculosis) is the causative agent of paratuberculosis, a chronic enteritis of ruminants. To control the considerable economic effect that paratuberculosis has on the livestock industry, a vaccine that induces protection with minimal side effects is required. We employed transposon mutagenesis and allelic exchange to develop three potential vaccine candidates, which were then tested for virulence with macrophages, mice, and goats. All three models i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 52 publications
3
39
0
2
Order By: Relevance
“…paratuberculosis ⌬ppiA), defective in the peptidyl-prolyl cis-trans-isomerase, showed a mild attenuated phenotype relative to the wild-type strain and resulted in limited tissue colonization following challenge with parental M. avium subsp. paratuberculosis strain (53). Alternatively, the attenuated M. avium subsp.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…paratuberculosis ⌬ppiA), defective in the peptidyl-prolyl cis-trans-isomerase, showed a mild attenuated phenotype relative to the wild-type strain and resulted in limited tissue colonization following challenge with parental M. avium subsp. paratuberculosis strain (53). Alternatively, the attenuated M. avium subsp.…”
Section: Figmentioning
confidence: 99%
“…paratuberculosis mutants (e.g., WAg915 and M. avium subsp. paratuberculosis ⌬leuD) as live attenuated vaccine candidates in the murine model of paratuberculosis (53,54). The mutant strain WAg915 (M. avium subsp.…”
Section: Figmentioning
confidence: 99%
“…Several attempts have been made to successfully produce mutant strains of M. avium subsp. paratuberculosis with vaccine potential by exploiting transposon mutagenesis and allelic exchange (17)(18)(19). The latter technology affords a method to select genes associated with virulence or function for gene disruption.…”
mentioning
confidence: 99%
“…paratuberculosis (Map) that induces sterile immunity against Johne's disease (JD) or prevents disease progression. These approaches have included development of killed whole vaccines, live attenuated, DNA and subunit vaccines and tests in different animal species (Bull et al 2007;Park et al 2008;Juste et al 2009;Kathaperumal et al 2009;Scandurra et al 2010;Bastida and Juste 2011;Stabel et al 2012;Faisal et al 2013). Although none of the vaccines induced sterile immunity they did slow disease progression and demonstrated that development of a vaccine that induces sterile immunity is feasible (reviewed in (Rosseels and Huygen 2008).…”
Section: Various Approaches Have Been Taken To Develop a Vaccine Tomentioning
confidence: 99%